Relationship between Low Birth Weight Neonate and Maternal Serum Zinc Concentration - Khadem, N (Kowsar, 2012)
BACKGROUND: Zinc deficiency can lead to clinically relevant disturbances in tissue functions and particularly important for birth weight of neonates. The aim of this study was to determine the relationship between serum zinc in pregnant women and the incidence of low birth weight (<2500 g) in their newborns. METHODS: This case-control study was done on women who delivered low birth weight infants (Cases), and normal birth weight infants (Controls). Blood samples got in all women within 5 minutes of delivery, and assessed the concentration of zinc using electrothermal atomic absorption spectrometry. Serum concentration of zinc was compared. RESULTS: One hundred and seventeen mothers were enrolled, of them, 65 cases were low birth weight infants (1845±472 g) and 52 were controls (3166± 435 g). Mothers in the case and control groups did not differ in age, body mass index, and socioeconomic or demographic factors. Maternal zinc concentration differed between cases and controls; 753.34±15 µg/l vs. 654.76±12 µg/l respectively. Maternal zinc differed between premature and full term deliveries. CONCLUSION: Maternal zinc concentration was shown to affect birth weight and prematurity.